Development of dual‐visible reporter assays to determine the DNA–protein interaction. (12th January 2023) - Sun, Huayu; Wang, Sining; Yang, Kebin; Zhu, Chenglei; Liu, Yan; Gao, Zhimin
SUMMARY: The application of DNA–protein interaction reporter assays for relational or ratiometric measurements within an experimental system is popular in biological research. However, the existing reporter‐based interaction assays always require special equipment, expensive chemicals, and a complicated operation. Here, we developed a DNA–protein interaction technology integrating two visible reporters, RUBY and UV‐visible GFP (eYGFPuv), which allows the expression of the cassette reporter contained cis ‐acting DNA element (DE) fused upstream of TATA box and RUBY, and a constitutive promoter regulating eYGFPuv in the same construct. The interaction of transcription factor (TF) and the DE can be detected by co‐expressed the cassette reporter and TF in tobacco leaves where the cassette reporter alone serves as a control. We also revealed that eight function‐unknown bamboo AP2/ERFs interacted with the DE of ANT‐AP2R1R2 (ABE), DRE (DBE), GCC‐box (EBE), and RAV1 binding element (RBE), respectively, which are consistent with the results by dual‐luciferase reporter assays. Thus, the dual‐visible reporters offer a convenient, visible, and cost‐saving alternative to other existing techniques for DNA–protein interaction in plants. Significance Statement: A DNA–protein interaction reporter assay has been developed by integrating two visible reporters, RUBY and eYGFPuv, which offers a convenient, visible, and cost‐saving alternative to other existing techniques for DNA–protein interaction in plants.